Kajian Eskatologis 1 Tesalonika 4:17 Mengungkap Fakta Pengangkatan - Samuel Lengkong (SCRIPTA: Jurnal Teologi dan Pelayanan Kontekstual, 2023)
Talking about the end times is a matter of hope for believers in Jesus Christ who are experiencing trouble and suffering so that later there will come a time of happiness, peace, and encouraging believers to always be ready to welcome the coming of Jesus Christ. In the midst of being a hope for Christians, there are many interpretations and phenomena about the end times that predict the coming of Jesus Christ and the rapture of God's people. This study uses qualitative research, in which the researcher collects as much theory and information from the literature as opinions, ideas, concepts and ideas that are appropriate to the research topic. This study aims to find and reveal the facts of the rapture of believers contained in 1 Thessalonians 4:17. In this study, by analyzing and exegesis a number of data, the researchers found and found that the appointment took place in a double reference and double interpretation manner, that is, both during the period after the writing of 1 Thessalonians (symbolic) and before the thousand year period there were some people believe or the church experiences the great tribulation (Revelation 6-19), the rapture takes place literally.